2016
DOI: 10.1053/j.seminoncol.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The Bayesian basket design for genomic variant-driven phase II trials

Abstract: Basket clinical trials are a new category of early clinical trials in which a treatment is evaluated in a population of patients with tumors of various histologic types and primary sites selected for containing specific genomic abnormalities. The objective of such studies is generally to discover histologic types in which the treatment is active. Basket trials are early discovery trials whose results should be confirmed in expanded histology specific cohorts. In this report, we develop a design for planning, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 8 publications
0
78
0
1
Order By: Relevance
“…The common definitions of each trial type based on literature [22,23] are shown in Table 1. However, as pointed out by Renfro and Sargent [23], the definitions of each trial type are not standardized [10,20,[35], [36], [37]], with possible overlaps between them that should be noted. For example, the NCI-MATCH trial, which will be mentioned in a later section, is a type that has aspects of both basket and umbrella trials.…”
Section: Basket Umbrella and Platform Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The common definitions of each trial type based on literature [22,23] are shown in Table 1. However, as pointed out by Renfro and Sargent [23], the definitions of each trial type are not standardized [10,20,[35], [36], [37]], with possible overlaps between them that should be noted. For example, the NCI-MATCH trial, which will be mentioned in a later section, is a type that has aspects of both basket and umbrella trials.…”
Section: Basket Umbrella and Platform Trialsmentioning
confidence: 99%
“…For example, Neuenschwander et al [55] developed the exchangeability–nonexchangeability (EXNEX) method, which is a robust mixture extension of the standard EX approach and allows each stratum-specific parameter to be exchangeable with other similar strata parameters or nonexchangeable with any of the similar parameter. Simon et al [56,57] developed a different kind of Bayesian design using two parameters, which one is specified as the prior probability that the response in each stratum is considered desirable activity and one is specified as the prior probability that the response probabilities are equal across strata. More recently, Chu and Yuan [58] developed the Bayesian latent subgroup design (BLAST), which accounts for patient heterogeneity.…”
Section: New Trial Designs In Master Protocol Trialsmentioning
confidence: 99%
“…A basket trial is typically conducted as a phase‐2 trial whose objective is to detect in which strata the targeted drug is efficacious or inefficacious. This is a discovery trial, rather than hypothesis testing (Simon, Geyer, Subramanian, & Roychowdhury, ). An actual example of such a basket trial is the BRAF‐V600 study, which is a phase‐2 trial that assesses the efficacy of vemurafenib in patients with BRAF‐V600 mutation‐positive cancer (Hyman, Puzanov, Subbiah, & Faris, ).…”
Section: Introductionmentioning
confidence: 99%
“…This issue may be anticipated, as it is well accepted that the environment and location in which a tumor develops may impact its mutational profile as well as differentially predict treatment response across similar profiles. To this end, many have noted that current clinical evidence is insufficient to conclude that molecular descriptors should replace histological tumor typing [18,22,41,47], and it has been suggested that future studies integrate anatomic with mutational and functional molecular profiling through the use of proteomic technologies [47] and explore multi-gene signatures with combination therapies [48].…”
Section: Limitations Of Basket Trialsmentioning
confidence: 99%
“…A number of authors have noted confusion regarding the definitions of these terms [16,19,22,39,41,42]; we attempt to harmonize some definitions here.…”
Section: Baskets Umbrellas and Platforms: Definitions And Terminologymentioning
confidence: 99%